Influence of vitamin C and E supplementation on the eradication rates of triple and quadruple eradication regimens for Helicobacter pylori infection - Demirci, Hakan; Uygun İlikhan, Sevil and Öztürk, Kadir and Üstündağ, Yücel and Kurt, Ömer and Bilici, Muammer and Köktürk, Furuzan and Uygun, Ahmet (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: In our study, we aimed to assess the effect of vitamin E and C supplementation to triple and quadruple Helicobacter pylori eradication regimens. Materials and Methods: Four hundred patients with H. pylori infection were classified into four groups. Patients in group A (n=100) received amoxicillin, clarithromycin, and lansoprazole for 2 weeks. In group B, patients (n=100) received vitamins C and E for a month, in addition to amoxicillin, clarithromycin, and lansoprazole for 2 weeks. Patients in group C (n=100) received amoxicillin, clarithromycin, lansoprazole, and bismuth subcitrate for 2 weeks, whereas those in group D (n=100) received vitamins C and E for a month, in addition to amoxicillin, clarithromycin, lansoprazole, and bismuth subcitrate for 2 weeks. H. pylori eradication was assessed with the C14 urea breath test 2 months after the end of the therapy. The eradication rate was assessed using per-protocol (PP) and intention-to-treat (ITT) analyses. Results: Three hundred forty-eight patients finished the study. The eradication of H. pylori was achieved in 63 of 84 patients (75%) by PP and 63 of 100 (63%) by ITT analysis in group A, 60 of 84 (71.4%) by PP and 60 of 100 (60%) by ITT analysis in group B, 72 of 89 (80.9 %) by PP and 72 of 100 (72%) by ITT analysis in group C, and 76 of 91 (83.5%) by PP and 76 of 100 (76%) by ITT analysis in group D. There was no remarkable change between groups A and B (p>0.05). Similar results were also found between groups D and C (p>0.05). Conclusion: This study revealed that supplementing vitamins C and E to either the triple or quadruple therapies did not provide an additional advantage for achieving significantly higher eradication rates for H. pylori.